2018
DOI: 10.1186/s12885-018-4604-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators of clinical cancer care for prostate cancer: a population-based study in southern Switzerland

Abstract: BackgroundQuality of cancer care (QoCC) has become an important item for providers, regulators and purchasers of care worldwide. Aim of this study is to present the results of some evidence-based quality indicators (QI) for prostate cancer (PC) at the population-based level and to compare the outcomes with data available in the literature.MethodsThe study included all PC diagnosed on a three years period analysis (01.01.2011–31.12.2013) in the population of Canton Ticino (Southern Switzerland) extracted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
3
8
2
Order By: Relevance
“…A set of QI representing crucial facets of the care given to patients diagnosed with PC was used by our research team, encompassing the clinical domains of diagnosis, pathology, and treatment. The QI were selected from a comprehensive list developed and validated by other researchers [ 6 , 10 , 11 ]. Further, the staging of the disease was registered based on the American Joint Committee on Cancer (AJCC) staging manual (8th edition) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of QI representing crucial facets of the care given to patients diagnosed with PC was used by our research team, encompassing the clinical domains of diagnosis, pathology, and treatment. The QI were selected from a comprehensive list developed and validated by other researchers [ 6 , 10 , 11 ]. Further, the staging of the disease was registered based on the American Joint Committee on Cancer (AJCC) staging manual (8th edition) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…QoC studies can typically assess the quality of care provided at the societal level, providing an accurate picture of the regional care pattern, free of sample bias. This could be done using the information from the cancer registries [ 6 ]. It is possible to document the quality of treatment delivered and offer regular feedback to healthcare professionals and decision-makers through specific quality indicators (QI), which are used for QoC studies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ticino Cancer Registry in Switzerland, one QI in their 13 PCa-related QIs focussed on men with mPCa. 3 They reported that 73.5% of patients with mPCa received androgen deprivation therapy (ADT) within 3 months of diagnosis. In the Danish registry, the sole indicator regarding men with mPCa demonstrated that 52% of patients in 2014 were receiving ADT within 6 months of diagnosis, 4 much lower than their pre-determined standard of ≥75% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…† 2 All men with metastatic PCa should have performance status recorded at an MDT meeting 3. In men with metastatic PCa, clinicians should screen for the presence of symptoms including pain, psychosocial distress (e.g.…”
mentioning
confidence: 99%